2022
DOI: 10.3390/ijms23073640
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-Mediated Knockout of miR-130b Affects Mono- and Polyunsaturated Fatty Acid Content via PPARG-PGC1α Axis in Goat Mammary Epithelial Cells

Abstract: MicroRNA (miRNA)-130b, as a regulator of lipid metabolism in adipose and mammary gland tissues, is actively involved in lipogenesis, but its endogenous role in fatty acid synthesis remains unclear. Here, we aimed to explore the function and underlying mechanism of miR-130b in fatty acid synthesis using the CRISPR/Cas9 system in primary goat mammary epithelial cells (GMEC). A single clone with deletion of 43 nucleotides showed a significant decrease in miR-130b-5p and miR-130b-3p abundances and an increase of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Goat milk is rich in fatty acids, which is the main reason for its unique healthcare function. Exploring the molecular mechanism of regulating goat milk fatty acid synthesis is an important basis for optimizing the composition and content of goat milk fatty acids [ 18 ]. Previous studies found that the miR-26 family promotes lipid metabolism in goat mammary epithelial cells, which may be mediated by the target INSIG1 [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Goat milk is rich in fatty acids, which is the main reason for its unique healthcare function. Exploring the molecular mechanism of regulating goat milk fatty acid synthesis is an important basis for optimizing the composition and content of goat milk fatty acids [ 18 ]. Previous studies found that the miR-26 family promotes lipid metabolism in goat mammary epithelial cells, which may be mediated by the target INSIG1 [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The CRISPR/Cas9 system achieves targeted gene editing through sgRNA, but because the mature sequence of miRNA only has about 22 nucleic acids, the CRISPR/Cas9 of a single sgRNA has less of an effect on miRNA genome editing, while the efficiency of double sgRNA is higher [ 19 ]. Previously, we found that a single miRNA was knocked out in GMECs using the CRISPR/Cas9 system with double sgRNA [ 18 , 20 , 21 ]. MiR-26a and miR-26b knockout cell lines were obtained by transfecting two double-sgRNA-containing vectors into GMECs, using puromycin for screening and cell monoclonal culture.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrobromide prevents the transport of the sterol regulatory element-binding protein cleavage-activating protein from the endoplasmic reticulum to the Golgi apparatus, thereby inhibiting the activation of SREBP2 [ 64 ]. A study showed that miR-130b significantly affects cholesterol production mediated by SREBP2 [ 65 ], and miR-33a targets SREBP2 to block the invasion and metastasis of NSCLC cells [ 66 ]. Some drugs, including artesunate and emodin, target SREBP2 to regulate lipid metabolism related to the MVA pathway and inhibit tumor growth [ 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…The extraction of total RNA from the lung tissue of the mice was achieved utilizing the TRIZOL reagent (Invitrogen, Carlsbad, CA, USA). RNA quality was examined by concentration detection, in which the absorbance ratio at OD260/OD280 was 1.8–2.0, and that at OD260/OD230 was 2.0–2.2 [ 34 ]. RNA integrity was determined through 18S and 28S rRNA analysis by gel electrophoresis ( Figure S3 ).…”
Section: Methodsmentioning
confidence: 99%